PROTOTIPE SISTEM PENGAMAN TANGGA BERJALAN TRAVELATOR BERBASIS ARDUINO UNO R3 - yoyo saputra; Imam agus faisal; agung setya pramana (Cahaya Bagaskara : Jurnal Ilmiah Teknik Elektronika, 2020)
Travelator machine is the result of technological advances, which at first people want to move from the ground floor to the upper floor or vice versa have to go up or down the steps one by one. But with a travelator machine, we just stand on the stairs so the travelator will take us up to the top floor or down the floor automatically. The use of a travelator in modern shopping venues needs to get more special attention. Nylon brushs in the right and left corners of the bottom of the travelator function as a safety limit for the use of the travelator. But many visitors take advantage of the nylon brushs to clean the dirt that clings to their shoes and slippers. The dirt causes extra maintenance on the engine and makes the engine life shorter. Using the Infrared Obstacle Detection Sensor, it is possible to detect objects such as feet that will be pinched and immediately the sensor gives an order to stop the travelator. However, because the sensor's emission on the transmitter has a range of 17 ° and the receiver has a range of 45 °, while the sensor area on the prototype is only 1cm, making the sensor range only about 15cm. Thus there is no more dirt coming from the travelator ladder